The intergenerational transmission of family violence: Mothers' perceptions of children's experiences and use of violence in the home. Issue 3 (17th February 2021) - Meyer, Silke; Reeves, Ellen; Fitz‐Gibbon, Kate
Abstract: Intimate partner violence (IPV) on average affects one in four women, with the majority of victim survivors identifying as mothers in national survey data. Children experiencing parental IPV are now equally understood as victims. Extensive research documents the short‐ and long‐term impacts of children's experiences of IPV on their safety and wellbeing. More recently, research has started to examine adolescent children's use of violence in the home as adolescent family violence (AFV). Contributing to this emerging body of research, we draw on narrative interview data from mothers who participated in a larger study on IPV, help‐seeking and the perceived impact on children to better understand how mothers make sense of children's use of violence in the home. Mothers identified an emergence of AFV in male children with childhood experiences of adult IPV. Although mothers' experiences of adult and adolescent violence highlight their dual victimisation, mothers frame their abusive children as victims rather than perpetrators. Implications for future research, policy and trauma‐informed practice are discussed.